Description of the final stadium larva of Heliocypha perforata perforata (Percheron), with discussion of the taxonomic characters of the larvae of the genus Heliocypha Fraser (Odonata: Zygoptera: Chlorocyphidae) - Xu, Qi-Han (Zootaxa, 2015)
The final stadium larva of Heliocypha perforata perforata is described and illustrated for the first time. It is characterized by having a row of filiform setae present laterally on distal half of prementum, 6-7 setae on the outer side of palpal lobe, very long lateral gills and distinct abdominal color pattern. The taxonomic characters of the larvae of the genus Heliocypha Fraser are discussed and summarized. Heliocypha larvae share a high similarity with Rhinocypha in general appearance and cannot be clearly distinguished from the latter in structure.